STRUCTURE-ACTIVITY RELATIONSHIPS AND SURFACE IMMOBILIZATION OF POLYCATIONIC ANTIMICROBIALS - Mohamad Widodo; Sophie Anggitta Raharjani (Arena Tekstil, 2020)
Antimicrobial agents have been the subject of scientific interest for the last few decades. However, the emergence of a novel coronavirus and pandemic that ensued has brought a new sense of urgency to the field of antibacterial research. The most urgent needs to mitigate the pandemic are self-disinfecting health equipment and antimicrobial protective equipment such as gowns for healthcare workers and face masks for the general public. At a time of high demand for antimicrobial products, understanding the mechanisms involved in antimicrobial polymers will be a benefit. In this review, the definition of antimicrobials and their classification according to the mode of action, as well as their chemical structure, were explained and used to build the fundamental understanding about antimicrobials and the working principles behind their action. The discussion continued with factors that affect the antimicrobial activity, which is the focus of the review.  The first part of the review deals with free antimicrobial polymers in solution. The effect of molecular weight, counterions, spacer length and alkyl chain to the efficacy of antimicrobial polymers are highlighted and discussed at length. Focus in the second part shifts towards surface-immobilized antimicrobial polymers and their methods of immobilization.